2007
DOI: 10.2174/157015907780866929
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiological Bases for Development of Pharmacological Treatments of Aggressive Disorders

Abstract: Violence and aggression are major causes of death and injury, thus constituting primary public health problems throughout much of the world costing billions of dollars to society. The present review relates our understanding of the neurobiology of aggression and rage to pharmacological treatment strategies that have been utilized and those which may be applied in the future. Knowledge of the neural mechanisms governing aggression and rage is derived from studies in cat and rodents. The primary brain structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 102 publications
1
58
0
7
Order By: Relevance
“…E.g. the lateral hypothalamus showed similar levels of activation in insect hunting rats and their feeding controls, despite the fact that this brain area is considered the most important control region of rat killing in cats and frog and mouse killing in rats [1,4,29]. According to our own observation, muricide and insect hunting are behaviorally different, which may explain these discrepancies.…”
Section: Introductionmentioning
confidence: 65%
“…E.g. the lateral hypothalamus showed similar levels of activation in insect hunting rats and their feeding controls, despite the fact that this brain area is considered the most important control region of rat killing in cats and frog and mouse killing in rats [1,4,29]. According to our own observation, muricide and insect hunting are behaviorally different, which may explain these discrepancies.…”
Section: Introductionmentioning
confidence: 65%
“…4 Neurobiologically, impulsive/affective aggression may be explained as a lack of equilibrium between prefrontal mechanisms of top-down control (orbitofrontal cortex and anterior gyrus cinguli) and the bottom-up limbic stimuli (amygdala and other limbic areas), in which several neurotransmitters, such as serotonin, dopamine, noradrenalin and others, may be involved and may, therefore, be managed pharmacologically. 5,6 Several studies have demonstrated that aggression is a result of the combination of socioenvironmental, psychological and biological factors, and that an environment favorable to personal development may modulate unfavorable genetic characteristics. 7,8 However, biological factors of aggressive behaviors may and should be carefully managed because of probable mid-and long-term impairments and the progression into severe psychiatric disorders in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Defensive rage and panic subsystems could reflect the activation of hypothalamic nuclei in response to alarming stimuli. Such processes clearly involve other vital brain centres such as the amygdala and the brain stem, notably the midbrain's periaqueductal gray matter (PAG) [140][141][142][143].…”
Section: Impulse Controlmentioning
confidence: 99%